CP-145 A school of asthma implemented in a paediatric ward: Impact on patients and family. (14th February 2016) - Pardo, A; Generet, M; Nachtergael, A; Devillez, A; De Meester, C; Ladha, K; Sténuit, S
Abstract : Background: Education of asthmatic patients is vital in the therapeutic process to improve the control of the disease, especially in children and in the adolescent population. In 2011, a close collaboration between a paediatrician and a clinical pharmacist led to the creation of a 'school of asthma' in the paediatric ward (SAPW) of our hospital. The SAPW is composed of a multidisciplinary team of healthcare professionals who aim to predominately teach the fundamentals on: (i) asthma pathophysiology, (ii) the pharmacology of inhaled medications for acute and maintenance therapy and (iii) inhaler technique. Purpose: To assess the effectiveness of an SAPW session of 3 h in improving the pathophysiological, pharmacological and technical knowledge of ambulatory asthmatic patients aged 6–20 years and their families (AAPF). Material and methods: We examined the SAPW sessions from years 2012 to 2015 (3–4 sessions/year, maximum 10 AAPF/session). Each session was carried out as follows: collection of participants' needs, open and interactive presentations, viewing of training videos, achievement of simulation exercises, distribution of useful documents, and questions and answers. Questionnaires surveying current pathophysiological, pharmacological and technical knowledge were distributed to AAPF before and after each SAPW session; the results were statistically tested by a two tailed paired t test. Questionnaires surveying AAPF satisfaction were also distributed after each SAPW session; possible scoring obtained was poor, satisfactory, good, very good or excellent. Results: 72 AAPF were recorded for their participation at the SAPW (n = 72). 96% of AAPF completed and returned all of the questionnaires. By comparing the results obtained before and after the SAPW sessions, we identified a statistically significant improvement in pathophysiological and technical knowledge of AAPF (p < 0.001). The improvement in pharmacological knowledge did not appear to be statistically significant as a high rate of correct answers (>84%) were obtained by the AAPF for these fundamentals before the SAPW sessions. The scores attributed at the end of sessions were satisfactory, good, very good and excellent for, respectively, 22%, 30%, 40% and 8% of AAPF. Conclusion: Based on high satisfaction rates for AAPF and on the significant positive impact regarding knowledge, the SAPW was confirmed as providing a useful educational programme. No conflict of interest.